The Existence of Traditional Handicrafts in Malang Raya as Part of Indonesian Cultural Heritage - Dhesti Anggriani, Swastika; Nurwiseso Wibisono, Muhammad; Deffinika, Ifan; Kurnia Ramadhani, Elvira (KnE Social Sciences, 2023)
Traditional handicrafts in Indonesia are one part of the seven elements of intangible cultural heritage based on the UNESCO Conference 2003. Currently, not everyone from the general public knows their area’s existence and types of traditional handicrafts. This study describes how the presence, number, and types of traditional handicrafts in Malang Raya are part of Indonesia’s cultural heritage. The research method used is a qualitative method with a descriptive type. The research location takes place in the Malang Raya region - including Malang City, Malang Regency, and Batu City. Data collection techniques used are observation, interviews, documentation, and recording. Primary data sources in this study were obtained from direct sources, and secondary data sources were from documentation, reference books, and relevant research journals. The technique of collecting data sources in this research is using the snowball sampling technique. The data analysis used is qualitative data analysis, which includes three stages: data reduction, data presentation, and conclusions. The results showed that traditional crafts in Malang Raya do still exist.. However, not many people know or are interested in these traditional crafts. Keywords: traditional handicrafts, Malang Raya, cultural herita